Rearing performance of Philosamia ricini (Eri silkworm) in different seasons of Ujjain district - Shubhangi Vaidya; Ulka Yadav (Environment Conservation Journal, 2014)
India has the unique distinction of being only country producing all the five commercially traded varieties of natural silk namely Mulberry, Eri, Muga, Temperate tasar and Tropical tasar. The silk produced by Philosama ricini is called Eri silk. Eri silk is known as Non Violence silk or Piece silk. It is also said to be Poor Person’s silk. The Eri silkworm (Philosamia ricini) is multivoltine, holometabolus, non-mulberry, completely domesticated and feed on castor (Ricinus communis) leaves.We observed the effect of different seasons on rearing performance of Eri silkworm in respect of different larval parameters (larval weight, larval length, ERR% and pupation) and cocoon parameter (cocoon weight, pupae weight, shell weight & shell %). Our findings clearly indicated that the rearing performance of Eri silkworm was better in spring season than winter and autumn season of Ujjain district M.P.